Employee Performance Effectiveness at the Makassar State Administrative Court Office - Jamaluddin Jamaluddin; Muh. Nursyam; Muh. Nasrullah (ASHA Publishing, 2024)
Effectiveness is the relationship between output and goals or it can also be said to be a measure of how far the level of output is, effectiveness is also often used to measure the success achieved by organizations or companies related to planned programs. Employee effectiveness is a key factor in ensuring the smoothness and quality of legal services provided. This study is qualitative descriptive research that aims to find out the picture of the effectiveness of employee performance at the Makassar State Administrative Court office. The data collection technique uses observation, interview, and documentation. The data analysis technique in this study uses data condensation techniques, data presentation, conclusion and verification. The results of the study show that the effectiveness of employee performance at the Makassar State Administrative Court office, seen as a whole, is good and effective. This can be seen from the fulfillment of the eight performance indicators, namely work quality, efficiency, work discipline, initiative, precision, leadership, honesty, and creativity. In an organization or agency, it can run well if employees understand their duties and responsibilities so that the services provided to the community can run well. Employees are a very important resource because employees are one of the elements of the apparatus that institutionally become part of government management to carry out their main tasks and functions in government, development, and service to the community. Services to the community by the government in all fields.